Pengembangan Media Circular Card untuk Membelajarkan Kosakata Bahasa Arab bagi Siswa Kelas V MI Nahdlatul Ulama "Putri" Malang - Atiqatul Musyarofah (Tarbiyatuna Kajian Pendidikan Islam, 2017)
This research was conducted with the aim to describe several things, covering the manufacture of circular card media product, display of circular card media product, how to use circular card media. The data collected by the researcher are validation data from the expert test of media and the test of the material, and the validation result from the field test that is from the teacher and the students of grade V of MI Nahdlatul Ulama "Putri" Malang. Media circular card that has been developed consists of 12 themes with 4 pairs of images and vocabulary on each theme. Third, the steps of its use are integrated by the learning stage, ie preliminary activities, core activities, and closing activities. In each stage of the learner the students are not only taught to the introduction of word vocabulary, but from the vocabulary students can make simple sentences from the vocabulary that have been taught by the teacher, or can also be developed in the form of dialogue where the vocabulary used in the dialogue comes from the vocabulary which has been taught that is from the media circular card.